Kepedulian Peserta Didik Terhadap Lingkungan Sekolah di SD Negeri 2 Jatipuro Trucuk - Asfi Alvian Nurfaizah; Hani Binti Rishadi; Dihan Nanda Hamidah; Nela Rofisian (GLOBAL SCIENTS PUBLISHER, 2024)
This study aims to determine the application of environmental care character at SD Negeri 2 Jatipuro Trucuk Klaten through various activities that support awareness and responsibility for environmental cleanliness. A descriptive qualitative approach was used in this study, with data obtained through interviews and observations. The results showed that activities such as Clean Friday, class picket, and joint tree planting became the main initiatives in shaping the character of environmental care. However, challenges such as the lack of awareness of some students in maintaining cleanliness are still found, for example littering or storing garbage in desk drawers. The role of educators is very important in providing reinforcement and habituation of environmentally friendly behavior. This study emphasizes that the development of environmentally friendly characters must be carried out continuously through the involvement of all school members to achieve optimal results. The findings are expected to be a reference for schools in improving and developing environmental education programs.